Evaluation of Mesiodistal Angulation of Maxillary Anterior Teeth in Incisal View Using Manual and Digital Methods: An In Vivo Study - Penumatsa, Narendra V; Kamath, Akshata G; Lahiri, Banibrata; Reddy, Upasana; Kashi, Ashika B; Shadaksharappa, Shashidhara H; Bamigdad, Malak S; Alwakeb, Rehab M (The journal of contemporary dental practice, 2024)
The aim of the present research was to assess the mesiodistal angulation of the maxillary anterior teeth utilizing Image J computer software, a Profile projector, and a Custom-made jig. A total of 34 subjects (17 males and 17 females) were chosen from a group of 18-30 years old with bilateral Angle Class I molars and canine relationships. One manual approach (Custom-made jig) and two digital methods (J computer software, a Profile projector) were used to record the mesiodistal angulation in incisal view. The individuals had alginate impressions made, and a facebow was used to capture the maxilla's spatial relationship with the cranium. The articulated cast with the help of mounting ring moved to the specially customized jig, then the angulations was measured in the incisal view after the casts were placed in a semi-adjustable articulator. Data were recorded and statistically analyzed. The mesiodistal angulation in the incisal view via three methods between the 17 males and 17 females has statistically significant different. Although the mesiodistal angulation for maxillary lateral incisor and canine did not show any statistically significant difference, the maximum and minimum values obtained were always greater in males in comparison with the females. This indicates that the positions of six maxillary anterior teeth in the males resulted in the creation of upward sweep of incisal edges of central and lateral incisors which was also referred to as "smiling line" producing masculine surface anatomy more squared and vigorous while feminine surface anatomy being more rounded, soft, and pleasant. There was no statistically significant difference between the right and left sides, indicating bilateral arch symmetry and the symmetrical place of the right teeth compared with the left side's corresponding teeth. On conclusion, according to the current study's findings, all three approaches can measure the mesiodistal angulations of maxillary anterior teeth in incisal view with clinically acceptable accuracy. The digital methods, which included using the Image J computer software and the profile projector, achieved more accurate results than the manual method. The outcomes of this study's mesiodistal angulations can be used as a reference for placing teeth in both fully and partially edentulous conditions. This study contributes to a better understanding of the importance of achieving the ideal occlusion in the Indian population by placing the maxillary anterior teeth at the proper mesiodistal angulation. How to cite this article: Shadaksharappa SH, Lahiri B, Kamath AG, . Evaluation of Mesiodistal Angulation of Maxillary Anterior Teeth in Incisal View Using Manual and Digital Methods: An In Vivo Study. J Contemp Dent Pract 2024;25(4):320-325.